Inovasi Terbaru pada Fotokatalis Karbon dalam Meningkatkan Kinerja Fotokatalitik: Systematic Literature Review - Mitranikasih Laia (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Photocatalysis is one of the environmentally friendly technologies with great potential to address global issues related to pollution and the demand for clean energy. However, limitations of conventional photocatalyst materials, such as low light absorption and high electron–hole recombination rates, have hindered optimal efficiency. This review highlights the role of carbon-based materials as the latest innovation in enhancing photocatalytic performance. Various forms of carbon materials, including graphene, carbon nanotubes (CNTs), carbon quantum dots (CQDs), and porous carbon, have been shown to improve charge separation, broaden the light absorption spectrum into the visible region, and enhance the structural stability of photocatalysts. Literature analysis indicates that the integration of carbon with semiconductors significantly increases pollutant degradation efficiency, cycle stability, and the potential application in renewable energy production. Moreover, the utilization of biomass waste as a source of porous carbon opens opportunities for more economical, sustainable, and eco-friendly technologies. This article provides a comprehensive overview of research progress, performance enhancement mechanisms, and future development directions of carbon-based photocatalysts, which are expected to contribute to innovative solutions in the fields of energy and environmental sustainability.